2014
DOI: 10.4028/www.scientific.net/amm.658.700
|View full text |Cite
|
Sign up to set email alerts
|

Parameter Identification and Modeling of a Pneumatic Proportional Valve with Applicability in Control Design of Servo-Pneumatic Systems

Abstract: The key element in a servo-pneumatic actuation system is the control valve. This paper presents a method for parameter identification and modeling the flow characteristic of a FESTO MPYE-5-1/8-HF-101B proportional valve. An experimental setup and a procedure for parameter identification is presented in the paper. Simulation and experimental results are in agreement and the model of the valve could be used in high-accuracy positioning control design of pneumatic servo-systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Furthermore, there is no exact information about the value specification of critical pressure ratio since the value of this parameter changes from valve to valve, even between the same type of valves. In other words, Harris et al 19 suggested the value of b as b = 0.23 whereas Van der Merwe et al, 21 Rad et al 22 and Rad and Hancu 23 all propose the value of b as a function of control signal ( b = f( u )). The parabolic change in the “ ii .…”
Section: Existing and Proposed Flow Modelsmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, there is no exact information about the value specification of critical pressure ratio since the value of this parameter changes from valve to valve, even between the same type of valves. In other words, Harris et al 19 suggested the value of b as b = 0.23 whereas Van der Merwe et al, 21 Rad et al 22 and Rad and Hancu 23 all propose the value of b as a function of control signal ( b = f( u )). The parabolic change in the “ ii .…”
Section: Existing and Proposed Flow Modelsmentioning
confidence: 99%
“…The parameters b and C are already presented in the manufacturer’s catalog. The discharge coefficient ( C d ) can also be determined by the relevant formulations as shown in detail in the study by Rad et al 22 These values can be useful when the standard or the improved flow models are utilized. However, there will be no need to use these pre-defined parameter values in the proposed model since the effect of these parameters will be expressed by the model parameters (i.e.…”
Section: Determination and Mapping Of Cprmentioning
confidence: 99%
See 3 more Smart Citations